NAMFREL in the Philippines: The rising of the citizen power - Khoo, Y.H.K.; Iskandar, A.S.I. (2014)
As the world’s first citizen-led election watchdog, National Citizen’s Movement for Free Elections (NAMFREL) sets as the pioneer when it comes to election monitoring particularly in the Southeast Asia region for their cause to strive for a wider space for the democracy. Therefore, it is particularly important to document and analyze the role of NAMFREL during the authoritarian regime of Ferdinand Marcos. This paper looks at the significance of elections as a pillar for democratic process especially the civil and political rights of citizens to monitor electoral process under the experience of authoritarian leadership. Election under the regime of Marcos has been tainted with fraud, intimidation, corruption, abuse of power, used of government machinery, money politics and a long list of unfairness, unclean and injustices. However the existence of NAMFREL helps to bring back the power to choose to the people and expose the hypocrisy of the flawed system.